2021
DOI: 10.1021/acsnano.0c10945
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Metals: From Plasmonic Properties to Applications in Enhanced Spectroscopy and Photocatalysis

Abstract: The field of plasmonics is capable of enabling interesting applications in different wavelength ranges, spanning from the ultraviolet up to the infrared. The choice of plasmonic material and how the material is nanostructured has significant implications for ultimate performance of any plasmonic device. Artificially designed nanoporous metals (NPMs) have interesting material properties including large specific surface area, distinctive optical properties, high electrical conductivity, and reduced stiffness, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 237 publications
3
145
0
1
Order By: Relevance
“…For example, it is possible to control the microstructure and pore sizes in nanoporous metals by controlling the conditions and strategies of synthesis [26]. Results presented above suggest that this control can be used to enhance the sorption capabilities of such nanoporous materials in addition to providing a way of controlling nanofluidic transport [27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible to control the microstructure and pore sizes in nanoporous metals by controlling the conditions and strategies of synthesis [26]. Results presented above suggest that this control can be used to enhance the sorption capabilities of such nanoporous materials in addition to providing a way of controlling nanofluidic transport [27].…”
Section: Discussionmentioning
confidence: 99%
“…Later, Shen et al [ 131 ] reported a relative humidity (RH) sensors based on this hybrid mode platform, which exhibited wavelength sensitivity of 1.16 nm %RH and a quick response time of a few seconds. Besides the ordered plasmonic nanostructures mentioned above, the disordered system without delicate design of structures is also promising for sensors with the advantages of low-cost and simple excitation schemes [ 132 ]. This system with rough surface can also increase the FOM through Fano-resonant transmission profile [ 133 ].…”
Section: Metastructure-based Plasmonic Sensorsmentioning
confidence: 99%
“…One growing use of W is as a high-temperature, absorber layer to increase the solar absorptivity and decrease the thermal emissivity of solar thermal collectors or receivers for various energy applications [ 1 , 5 , 6 , 7 ]. Particularly, creating plasmonic nanostructured metals (nanorods, nanoparticles, nanoporous films) is of great interest as they augment the absorption of electromagnetic radiation over a tunable range of UV to near IR [ 8 , 9 ]. Different synthesis methods have been used to manufacture W films and coatings capable of modifying the solar absorptance of these surfaces.…”
Section: Introductionmentioning
confidence: 99%